Once again on loading and capacity selection of autotransformers in transmission grids - Vasilenko Nikita; Misrikhanov Misrikhan; Shuntov Andrey (E3S Web of Conferences, 2023)
The aspects which have a bearing upon selection of capacity of autotransformers, such as load graphs, permissible temperature characteristics, n-1, n-2 modes, are considered. On the basis of statistical analysis suggestions for improving the current method of capacity selection of autotransformers in transmission grids are given.